The Bandung and Braunschweig Twin City Campaign as a Diplomatic Communication Strategy from the Perspective of Maqashid Syariah - Nada Arina Romli; Noprita Herari; Mayang Puti Seruni (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: Bandung has formed numerous international alliances. The city of Bandung promotes international cooperation with cities from other countries that share a common vision, namely the aspiration to advance the growth of both entities. This engagement is referred to as sister city collaboration. Methods: This study use qualitative research with with case study analysis This research uses the theory of construction of reality and conceptualization of public diplomacy. Results: The result of this study is during the 60 years of bilateral cooperation that have been carried out, there have been 7 aspects of development carried out in the sister city campaign between Bandung and Braunschweig as well as 17 programs that have been carried out as part of the communication diplomacy campaign between Bandung and Braunschweig. Conclusion and suggestion: This study aims to explore the sister city campaign of Bandung and Braunschweig and analyze the diplomatic communication strategies carried out in the sister city campaign of Bandung and Braunschweig. This study does not examine the impact of the Bandung and Braunschweig twin city program on society and city development. This research provides benefits as a reference for institutions to develop collaborative city programs that have a greater impact on the community.